New genera and species of felt scales (Hemiptera: Coccomorpha: Eriococcidae), with descriptions of new species and immature instars of described species - Miller, Douglass R.; Stocks, Ian C. (Zootaxa, 2022)
In this work, emphasis is placed on the Eriococcidae (Hemiptera: Coccomorpha) of the Nearctic Region including the immature instars of many species not previously described, two new genera (Carphococcus Miller and Stocks and Ypofloiococcus Miller and Stocks), and 11 new species (Acanthococcus pennyae Miller and Stocks, Carph. apodus Miller and Stocks, Carpochloroides eugeniae Miller and Stocks, Ovaticoccus betsyae Miller and Stocks, Ov. gordoni Miller and Stocks, Ov. haigi Miller and Stocks, Ov. maryfoleybensonae Miller and Stocks, Ov. telotrichus Miller and Stocks, Ov. tuttlei Miller and Stocks, Ov. villanuevorum Miller and Stocks and Y. libeauae Miller and Stocks). In addition to the new taxa, descriptions and illustrations are provided for adult females, adult males and/or immature instars of Ac. arenosus (Cockerell), Ac. coccineus (Cockerell), Ac. dennoi Miller and Miller, Ac. gallicolus (Cockerell & Rohwer), Ac. hoyi Miller and Miller, Ac. kemptoni (Parrott), Apezococcus idiastes Ferris, Carpo. mexicanus Ferris, Cryptococcus fagisuga Lindinger, Cr. williamsi Kosztarab and Hale, Hypericicoccus hyperici (Ferris), Ov. agavacearum Pellizzari and Kozár, Ov. agavium (Douglas), Ov. cornutus (Ferris), Ov. densus (Miller), Ov. eriogoni (Miller), Ov. exoticus Pellizzari and Kozár, Ov. neglectus (Cockerell), Ov. peruvianus (Granara de Willink & Díaz), Ov. salviae Miller, Ov. sanguineus (Miller), Ov. tippinsi Miller and Miller, Ov. variabilis Miller, Spiroporococcus braggi (Cockerell & Robinson), S. yuccae (Ferris) and Xerococcus foquieriae Ferris. Lectotype designations are made for Ap. idiastes. Carpo, mexicanus and H. hyperici. New collection data are provided for Ov. californicus McKenzie, Ov. johnsoni (Miller), Ov. mackenziei Miller, Ov. parvispina (Chaffin) and Ov. viscosa (Kondo). Dichotomous keys are given for: determination of most eriococcid instars of both sexes; Nearctic genera of the Eriococcidae based on adult females; adult females, second-instar females, second-instar males, and first-instar nymphs of Ovaticoccus Kloet 1944; and the seven species of Acanthococcus Signoret 1875 treated here, based on first-instar nymphs. Oregmopyga Hoy 1963 and Cornoculus Ferris 1955 are treated as junior subjective synonyms of Ovaticoccus. Atriplicia Cockerell and Rohwer 1909 has been placed previously as a junior synonym of Eriococcus but here is regarded as a junior subjective synonym of Acanthococcus. We treat 44 species; new descriptions are provided for 101 treated instars, and detailed line drawings are given for all but three of them. The following species, listed in ScaleNet as occurring in the Nearctic Region, are transferred to Acanthococcus from Eriococcus Targioni Tozzetti 1868: Acanthococcus actius Miller and Miller 1993 rev. comb.; Ac. arenariae Miller and Miller 1993 rev. comb.; Ac. barri Miller 1991 rev. comb.; Ac. beshearae Miller and Miller 1993 rev. comb.; Ac. dennoi Miller and Miller 1993 rev. comb.; Ac. droserae Miller, Liu and Howell 1992 rev. comb.; Ac. epacrotrichus Miller and Miller 1992 rev. comb.; Ac. froebeae Miller 1991 rev. comb.; Ac. gallicolus (Cockerell & Rohwer 1909) comb. n.; Ac. hoyi Miller and Miller 1992 rev. comb.; Ac. mackenziei Miller and Miller 1992 rev. comb.; Ac. macrobactrus Miller and Miller 1992 rev. comb.; Ac. megaporus Miller and Miller 1993 rev. comb.; A. mesotrichus Miller and Miller 1993 rev. comb.; Ac. microtrichus Miller and Miller 1992 rev. comb.; Ac. monotrichus Miller and Miller 1993 rev. comb.; Ac. ophius Miller and Miller 1993 rev. comb.; Ac. stauroporus Miller and Miller 1992 rev. comb.; Ac. washingtonensis Miller and Miller 1992 rev. comb.; and Ac. whiteheadi Miller 1991 rev. comb. In addition, two species are transferred to Acanthococcus from Rhizococcus Signoret: Ac. coccineus (Cockerell 1894a) rev. comb. and Ac. kemptoni (Parrott 1900) rev. comb. Three images of water color paintings by Mary Foley Benson are included.